ADOPTION OF ARTIFICIAL INTELLIGENCE IN THE PHILIPPINE HOTEL AND LEISURE INDUSTRY: AN ASSESSMENT - Marierose P. Valenzuela; Lorena H. Garcia; Ismaela Bawica; Wendy Sadang; Eduardo R. Lalas (Acta Informatica Malaysia)
Artificial Intelligence has been a headline nowadays, it makes human work easier and faster. Organizations adopted this kind of technology to keep up with the demand of globalization and the hotel and leisure industry is amongst to integrate AI to its business model. Highly modernized hotels are more coveted to choose by customers due to their expectation of the excellent services they can be provided. This paper looks on the status of the adoption of artificial intelligence in the hotel and leisure industry in the Philippines as well as its capacity to take full advantage of the perceived benefits of the said technology in the future. It is anchored on Roger’s Innovation Diffusion Theory (IDT), and it rests on the underpinning for comprehending innovation adoption and the elements that influence an individual’s decision to accept a new technology. This research employed qualitative design using secondary data from research journals and articles. It focused on the relative advantage of artificial intelligence in general, efficiency, revenue enhancement, investment cost, reputation management, competitive intelligence, compatibility and complexity as the future in the hospitality, specifically in hotel and leisure industry.